2020
DOI: 10.1089/rej.2020.2309
|View full text |Cite
|
Sign up to set email alerts
|

The Danger of Being Too Sympathetic: Norepinephrine in Alzheimer's Disease and Graying of Hair

Abstract: Although alterations in the sympathetic nervous system (SNS) with age have been reported, and serious degenerative diseases of the autonomic nervous system such as multiple system atrophy are more likely to strike older people, connections between dysregulated adrenergic receptors and age-associated diseases and phenotypes have not been well studied. Two recent reports suggest that SNS may be more closely connected than previously appreciated. First, low nanomolar concentrations of Alzheimer's disease (AD)-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Blocking NE sympathetic nerve system (SNS) signals preserves hair pigmentation in stressed animals. Increased SNS activation has a severe irreversible effect on homeostasis in greying of hair and Alzheimer’s disease [ 132 ].…”
Section: Amines Neurotransmitters and Their Receptors In Skin Pigmentation Diseasesmentioning
confidence: 99%
“…Blocking NE sympathetic nerve system (SNS) signals preserves hair pigmentation in stressed animals. Increased SNS activation has a severe irreversible effect on homeostasis in greying of hair and Alzheimer’s disease [ 132 ].…”
Section: Amines Neurotransmitters and Their Receptors In Skin Pigmentation Diseasesmentioning
confidence: 99%
“…While hair graying is predominantly associated with chronological aging, there is considerable variation, both inter-individual and based on genetic background, in the onset and progression of graying [5,6]. Hair graying is a multifaceted process influenced by a combination of genetic, environmental, and age-related factors [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is not least because the study of greying permits one to observe and interrogate gerontobiology of a uniquely accessible and experimentally tractable human mini‐organ found throughout the human integument. Moreover, an increasing number of animal and human studies have identified grey hair as an age‐independent predictor of serious extracutaneous pathology, including Alzheimer's disease (Mendelsohn & Larrick, 2020), Parkinson's disease (Jucevičiūtė et al ., 2019) and cardiovascular disease (Elfaramawy et al ., 2018), raising suspicion that hair greying may indeed act as an important indicator of systemic ageing‐associated pathology. As we grow closer to explaining this poorly understood phenomenon, it is timely to revisit critically what is known about the biology of hair greying today.…”
Section: Introductionmentioning
confidence: 99%